Early Pancreatic Ductal Adenocarcinoma Survival Is Dependent on Size: Positive Implications for Future Targeted Screening. Issue 7 (August 2016) - Hur, Chin; Tramontano, Angela C.; Dowling, Emily C.; Brooks, Gabriel A.; Jeon, Alvin; Brugge, William R.; Gazelle, G. Scott; Kong, Chung Yin; Pandharipande, Pari V.
Abstract : Objectives: Pancreatic ductal adenocarcinoma (PDAC) has not experienced a meaningful mortality improvement for the past few decades. Successful screening is difficult to accomplish because most PDACs present late in their natural history, and current interventions have not provided significant benefit. Our goal was to identify determinants of survival for early PDAC to help inform future screening strategies. Methods: Early PDACs from the National Cancer Institute's Surveillance, Epidemiology, and End Results Program database (2000–2010) were analyzed. We stratified by size and included carcinomas in situ (Tis). Overall cancer-specific survival was calculated. A Cox proportional hazards model was developed and the significance of key covariates for survival prediction was evaluated. Results: A Kaplan-Meier plot demonstrated significant differences in survival by size at diagnosis; these survival benefits persisted after adjustment for key covariates in the Cox proportional hazards analysis. In addition, relatively weaker predictors of worse survival included older age, male sex, black race, nodal involvement, tumor location within the head of the pancreas, and no surgery or radiotherapy. Conclusions: For early PDAC, we found tumor size to be the strongest predictor of survival, even after adjustment for other patient characteristics. Our findings suggest that early PDAC detection can have clinical benefit, which has positive implications for future screening strategies.